A comparative analysis of primary stenting and optimal balloon coronary angioplasty in acute myocardial infarction. Six month results from the STENT PAMI trial - Mattos,Luiz Alberto (2000)
OBJECTIVE: To compare the outcome of balloon PTCA with final coronary stenosis diameter (SD) <=30%, with elective coronary stenting. METHODS: We performed a comparative analysis of the 6 month outcomes in patients treated with primary stenting and those who obtained an optimal balloon PTCA result treated during the first 12 hours of AMI onset included in the STENT PAMI randomized trial. RESULTS: The results were analysed into 3 groups: primary stenting (441 patients, SD=22±6%), optimal PTCA (245 patients), and nonoptimal PTCA (182 patients, SD= 37±5%). At the end of the 6 months primary stent group presented with the lowest restenosis(23 vs. 31 vs. 45%, p=0.001, respectively). Ischemia-driven target vessel revascularization rate (TVR) (7 vs. 15.5 vs. 19%, p=0.001, respectively). CONCLUSION: At the 6 month follow-up, primary stenting offered the lowest restenosis and ischemia-driven TVR rates. Compared to optimal balloon PTCA. Nonoptimal primary balloon PTCA pts (SD=31-50%), had the worst late angiographic outcomes and should be treated more actively with coronary stent implantation.